Four cancers related to HPV 16 infection in a 34-year-old woman - Kędzierawski, Piotr; Kopczyński, Janusz; Misiek, Marcin; Góźdź, Stanisław (Medical Studies/Studia Medyczne, 2017)
Human papilloma viruses are widespread among people. Two hundred subtypes of these viruses have been described. Most of the infections are not clinically relevant. Long-term infection by some high sub-type of human papilloma virus, however, can lead to pre-invasive and invasive cancers of urogenital organs, head and neck region, and skin. The paper presents the case of 34-year-old woman in whom four cancers associated with infection with human papilloma virus subtype 16 were diagnosed. The patient was treated with surgery and radiotherapy for cancers of the vulva, the perianal area, fingers, and cervix. This paper describes the course and outcome of the treatment.